Fertirrigation formation of rocket seedlings in different substrates - Ensinas, Simone Cândido; Monaco, Kamila de Almeida; Borelli, Aline Baptista; Scalon, Silvana Quintão; Silva, Eulene Francisco da (Revista de Ciências Agroveterinárias, 2013)
The development of specialized production and marketing of vegetable seedlings has motivated farmers to adopt new technology and crop culture, such as substrate utilization and commercial use of fertirrigation. Thus, the objective of this research was to evaluate different types of substrates with different doses of liquid fertilizer on the formation of rocket seedlings. The experiment was conducted at the Federal University of Grande Dorados - UFGD, Dourados, MS. The experimental design was randomized blocks in factorial scheme 4x3x4, with four replicates with four doses of liquid fertilizer Yogen5® 0, 2.5, 5.0, 10.0 mL L-1 and three substrates: BioPlant®, Vitaplan® commercial humus and oxisol. Sowing in polypropylene with 128 cells by placing three seeds to each cell at a depth of 1 cm. There were two fertirrigations at 17 and 27 days after sowing. At 34 days after sowing the chlorophyll content, leaf number, shoot length, root length, stem diameter, total fresh weight, dry weight and total content of nitrogen, phosphorus and potassium leaf were evaluated. Fertirrigation interfered with the development of rocket seedlings, providing an increase in the number of leaves, shoot length, stem diameter, root length and total fresh and dry weight. The use in oxisol as substrate was not effective in promoting germination of rocket seedlings.